The Implementation of Peer Assessment in Teaching Writing of Application Letter to Vocational High School Students (RETAIN, 2020)
This study was focused on the teacher perspective that teach application letter using stages of peer assessment. There are four stages that could be explained in this research, the first is teacher’s criteria, peer assessment classroom design, teacher’s classroom management, and also teacher’s evaluation of text which is students’ product. The teacher should be followed all of the stages for the best result of teaching. This research was conducted in order to find out whether the teacher follows all of the steps in sequence of peer assessment or he does not. This study is design in qualitative research because there is an observation and field note. This research was conducted the subject of this study that is a vocational high school who has the standard curriculum about application letter. The observation was written in observation checklist with note. Then, there a student’s product of application letter that checked and corrected by their peer. The result of this study showed that peer assessment stages has implemented by the teacher in his teaching. He used a worksheet to keep the teaching on track. But, this study found that some of students didn’t correct the error. Some of the students didn’t understand which one the error that should be corrected by them. Other that the student felt bad to making a correction of their friend. Key words : peer assessment, application letter, teaching writing.